EUROCON 2007 - The International Conference on "Computer as a Tool" 2007
DOI: 10.1109/eurcon.2007.4400579
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation in Stochastic Differential Equation Driven by Fractional Brownian Motion

Abstract: Paper presents a methodology for estimating the parameters of stochastic differential equation (SDE) driven by fractional Brownian motion (fBm). The main idea is connected with simulated maximum likelihood. To develop this methodology two important questions: generation the fBm sample paths with different Hurst parameter values and Hurst parameter estimation methods are studied. Effectiveness of methodology is analyzed through Monte Carlo simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In our experience, the aforementioned estimators work only when estimated from the data on fractional Brownian motion, but unfortunately, in the SDE context, such data are not available. Simulation studies reported in Filatova et al (2007) first estimate H from simulated fractional Brownian motion, and then estimate the other parameters given such estimate of H. In realistic situations this is of course not possible.…”
Section: Discussion On Existing Attempts Regarding Inference In Fract...mentioning
confidence: 99%
“…In our experience, the aforementioned estimators work only when estimated from the data on fractional Brownian motion, but unfortunately, in the SDE context, such data are not available. Simulation studies reported in Filatova et al (2007) first estimate H from simulated fractional Brownian motion, and then estimate the other parameters given such estimate of H. In realistic situations this is of course not possible.…”
Section: Discussion On Existing Attempts Regarding Inference In Fract...mentioning
confidence: 99%
“…In order to introduce the model for the data description we found the parameters of fBm, using methodology presented in (Filatova, 2008). There was only one significant parameter 0.4501  H (with standard deviation 0.0073 ), which allowed to select a model of the biomass population, namely Next to find estimates of (38) we used ideas of identification methods (Filatova & Grzywaczewski, 2007;Filatova et al, 2007) …”
Section: Examplementioning
confidence: 99%